1998
DOI: 10.1002/(sici)1097-4547(19980601)52:5<584::aid-jnr10>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone regulates the expression of the MAL proteolipid, a component of glycolipid-enriched membranes, in neonatal rat brain

Abstract: Detergent-insoluble glycosphingolipid-enriched membranes (DIGs) have been involved in the sorting and transport of specific proteins during oligodendrocyte maturation. The MAL (MAL, MVP17, VIP17) proteolipid, an integral membrane protein present in DIGs in mature oligodendrocytes, has been proposed as a component of the machinery for DIG-mediated transport in a restricted pattern of cell types including myelinating cells. We have previously shown that thyroid hormone regulates the expression of the myelin prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Progress in our understanding of thyroid hormone action in brain development over recent years has been made possible by the recognition of the central role of triiodothyronine in mediating thyroid hormone action and the recognition of specific nuclear receptors in target tissues as demonstrated by displacement studies. The cloning of the receptors and receptor variants has enabled investigators to undertake detailed analyses of the biochemical events that underlie the physiological and pathological action of thyroid hormone (TH) [24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Role Of Nutrients In Brain Organogenesis (Folate and Iodine)mentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in our understanding of thyroid hormone action in brain development over recent years has been made possible by the recognition of the central role of triiodothyronine in mediating thyroid hormone action and the recognition of specific nuclear receptors in target tissues as demonstrated by displacement studies. The cloning of the receptors and receptor variants has enabled investigators to undertake detailed analyses of the biochemical events that underlie the physiological and pathological action of thyroid hormone (TH) [24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Role Of Nutrients In Brain Organogenesis (Folate and Iodine)mentioning
confidence: 99%
“…The expression of the MAL gene is down-regulated by hypothyroidism and up-regulated by hyperthyroidism in the myelinated regions of the brain. The MAL (MAL, MVP17, VIP17) proteolipid, an integral membrane protein, has been proposed as a component of the machinery necessary for myelin formation during oligodendrocyte maturation [37].…”
Section: Role Of Nutrients In Brain Organogenesis (Folate and Iodine)mentioning
confidence: 99%
“…A possible site for phosphorylation of tyrosine residue 162 located in the loop between the fourth and fifth TM segments has also been identified. Significant similarity at the amino acid sequence level was only found to the MAL family of hydrophobic proteins, integral membrane proteins present in glycolipid-rich membranes in mature oligodendrocytes [35] and associated with human T cell differentiation [36]. The homology is between four stretches of approximately 20 amino acids representing the four TM-spanning domains present in the MAL protein and the first four TM domains in the MYADM protein.…”
Section: Computer Analysis With Myadmmentioning
confidence: 99%
“…MAL appeared even somewhat later ; we observed a delay of ~2‐3 days for mRNA and ~5‐6 days for MAL protein compared with MBP and PLP. Recently, it has been shown that MAL gene expression is regulated by thyroid hormone, as is known for many myelin proteins (Pombo et al, 1998). Our results suggest, however, the presence of a specific signal that determines the late onset of MAL expression, in addition to general stimuli.…”
Section: Mal Is Expressed Late During Cns Myelinationmentioning
confidence: 99%